Tradisionalisme dalam arsitektur Kolonial Belanda di kota Gorontalo, kasus studi: kawasan Kota tua kota Gorontalo - Andi Imelda Chanrasari; Nurmiah; Umar (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2018)
Humans basically cannot break away from the past which gave birth to the thoughts and values. These thoughts and values passed down continuously without any or with very little change that they become the customs and culture of the people. This kind of understanding is called traditionalism. It is assumed that traditionalism also exists in architecture as a product of human culture. Gorontalo as a rapid growing city during the Dutch colonial period kept a number of buildings from that era. The Dutch colonial buildings are results of Dutch culture either in their pure form or those that have been combined with traditional culture and the condition of the surrounding environment. The results showed that traditionalism in Dutch colonial architecture has an influence in the city of Gorontalo. These influences can be found in terms of the design of the floor plan, the shape of the building, the shape of the roof, the shape of the openings and the use of ornaments in buildings. © 2018 Andi Imelda Chanrasari, Nurmiah, Umar